To what extent does terrorism build a nation? : Approaches to the Basque case - López Romo, Raúl (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2022)
Much has already been written about Basque terrorism. Here, I review a group of studies that address a specific problem: the relationship between this form of political violence and processes of mass nationalisation. Much of the existing work has comprised micro-analyses, meaning there is still room for further original research, whether from a historical or other disciplinary standpoint. I shall focus on a specific case which has not previously been analysed: the evolution of constituencies in the Basque Country and Navarre where traditionalism, with its militant Catholic and Spanish nationalist component, obtained excellent electoral results in the 1930s. However, after Franco’s dictatorship, many voters switched their allegiance to vote for nationalist leftist options such as HB, the political wing of ETA.